Participação do sistema endocanabinoide na neuromodulação da neuropatia sensitiva periférica induzida por oxaliplatina em camundongos - Pereira, Anamaria Falcão (2020)
Oxaliplatin is associated with neurotoxicity that is expressed as a peripheral sensory neuropathy (PSN). Endocannabinoid system is known as a modulator of the nociceptive pathway, so that cannabinoid compounds have been investigated for the analgesic effect. This study evaluated the participation of endocannabinoid system in the neuromodulation in the PSN of oxaliplatin. PSN was induced through oxaliplatin injection (2 mg/kg, i.v., twice a week, 9 injections), for 28 days, in Swiss male mice (six weeks). CB1 and CB2 expression also was evaluated in dorsal root ganglion (DRG), spinal cord (SC), trigeminal ganglion (TG), trigeminal spinal tract (Sp5C), periaqueductal gray (PAG) after oxaliplatin injections. Cannabidiol (10 mg/kg, p.o.) or CB1/CB2 non-selective agonist (WIN 55,212-2; 0,5 mg/kg, s.c.) or AM251 (CB1 antagonist) or AM630 (CB2 antagonist) (3 mg/kg, i.p.) were administered before oxaliplatin injections. Mechanical and thermal nociceptive tests were performed, once a week, for 56 days. To assess the possible cannabimimetic effects of cannabidiol, rota rod, catalepsy and hot plate tests were accomplished. The c-Fos expression was evaluated in DRG and SC after pharmacological modulation of endocannabinoid system. The results showed that oxaliplatin increased the expression of CB1 (P < 0.05) in non-neuronal cells of the DRG and SC, on the 28th experimental day, and in neuronal cells of the TG (28th experimental day) and of the Sp5C and ventrolateral PAG (28th and 56th experimental days). The expression of CB2 was not observed in the analyzed tissues. Cannabidiol attenuated mechanical hyperalgesia and prevented the increase of c-Fos expression associated with oxaliplatin in the DRG and SC (28th experimental day) (P < 0.05), without inducing cannabimetic effects. WIN 55, 212-2 prevented mechanical hyperalgesia and cold allodynia and inhibited the increase of the expression of c-Fos associated with oxaliplatin (28th experimental day) (P < 0.05). AM251 anticipated the cold allodynia from the 21st day to the 14th day (P < 0.05), but did not interfere with the c-Fos expression, while AM630 did not cause alterations in the nociceptive responses provoked by oxaliplatin, but decreased the c-Fos expression in the spinal cord (P < 0.05). Thus, endocannabinoid system may play a protective role in the pathophysiology of oxaliplatin PSN, with the CB1 receptor having an important role in this action.